Some effects of praise during the escape condition of the functional analysis. (17th December 2020) - Weyman, Jennifer R.; Bloom, Sarah E.; Campos, Claudia; Garcia, Anna R.
Abstract: Many researchers provide praise for complying with demands during the escape condition of the functional analysis (FA). However, praise may function as a reinforcer for some individuals which may reduce the aversiveness of task presentation or increase behavior that competes with problem behavior (e.g., compliance with demands). In general, this may result in lower or less stable levels of problem behavior and decrease the efficiency of the FA. Thus, the purpose of the current study was to evaluate some effects of praise on the rate of problem behavior and compliance during the escape condition of the FA in children diagnosed with autism spectrum disorder. We found that praise did not affect the rate of problem behavior but did increase compliance in three of five subjects. The results of the study and implications for the assessment of problem behavior are discussed.